Auditory Function After Spinal Anesthesia. Issue 3 (May 1993) - Wang, Lars Peter; Lundberg, Johan; Magnusson, MÅns; TÖrnebrandt, Kenneth
Abstract : Objective: To determine the effect of spinal anesthesia using 26-gauge needles on hearing. Methods: Eighteen male patients undergoing transurethral resection of the prostate (TURP) or other transurethral procedures under spinal or epidural anesthesia were studied prospectively to reveal possible auditory side effects of dural puncture or absorption of irrigation fluid to the blood stream. Measurement of auditory function by pure tone, Bekesy and speech audiometry, and measurement of serum concentrations of sodium, potassium, urea, and glucose were performed preoperatively and postoperatively. Clinical examination of cranial nerve functions was performed postoperatively. Results: No mean change in hearing ability was seen in any group. One patient had severe, transient, low-frequency hearing loss with simultaneous severe postdural puncture headache. A statistically significant postoperative fall in serum osmolarity was noted in the epidural TURP group. Conclusion: Transient, severe hearing loss may still occur after spinal anesthesia using a 26-gauge needle. Minor hearing loss does not seem to be a problem with this needle size.